Legalitas Perjanjian Tidak Tertulis Arisan Online Ditinjau Dalam Kitab Undang-Undang Hukum Perdata - Adawiyah Nasution; Farrel Maulana; Haya qonita (UNES Law Review, 2023)
Online saving club is a group of people who use social media as a tool to raise money regularly at any given period. Saving club is recognized as an agreement even though it is often done. This online gathering is only done by agreement between several parties who participate in the gathering and is not written. If in the future there are problems such as defaults, it is very difficult to prove the form of the agreement is not written so that to resolve the problem, including the recognition of the parties participating in the social gathering. For this reason, this study will discuss what exactly is the position of the verbal agreement electronically and how its legal force is and what legal remedies are taken in the event of a breach of contract. This research was conducted by reviewing and focusing on the application of "Normative Juridical" legal rules, so the method used in this research is the normative juridical method related to civil law laws, especially the Legality of the Unwritten Agreement on Online Saving Club. The unwritten agreement in the online social gathering is legal and binding for the maker based on the principle of freedom of contract. The unwritten agreement in this online social gathering still has legal force with the backwardness of legal evidence in accordance with the ITE Law. The legal consequences of default are compensation and other legal remedies that have been agreed at the beginning of the agreement.